A influência da espiritualidade nas relações no trabalho: um estudo etnográfico em uma escola confessional integral - (:unkn) unknown (Universidade Federal do Pampa, 2024)
The research aimed to analyze how spirituality practices influence work relationships in a religious school organization. The method used was ethnography, with a qualitative approach, including semi-structured interviews with teachers, staff, and managers, as well as observations of moments of spirituality promoted in the institution. The results indicate that spirituality plays a crucial role in promoting interpersonal bonds, building a welcoming environment, and strengthening ethical and human values among employees. Participants report significant experiences during moments of reflection and meditation, highlighting the importance of feeling part of a community that values spirituality. However, the research also revealed challenges, such as management that subtly demonstrates the manifestation of its religious beliefs in the practices developed, as well as some individuals who do not feel comfortable participating in these practices. Thus, this work not only contributes to the literature by deepening the understanding of spirituality and work, but also proposes ways for faith-based organizations to implement spiritual practices in an inclusive and effective way. In addition, the study provides a basis for the development of institutional policies that respect and embrace diversity, reinforcing the role of spirituality as a pillar of a more just, empathetic, and supportive organizational culture
The influence of spirituality on work relationships: an ethnographic study in a comprehensive confessional school
Keywords: Espiritualidade; Religião; Trabalho; Relações interpessoais; Escola confessional; Spirituality; Religion; Transcendent; Interpersonal relationships; Confessional school; CIENCIAS SOCIAIS APLICADAS